The association between intranasal esketamine and treatment-emergent iInsomnia in the treatment of treatment-resistant major depression: a meta-analysis : brief report - Türkmen, Cagdas; Boesjes, Rutger; Zandbergen, Anne-Fleur; Kamphuis, Jeanine; Viechtbauer, Wolfgang; Schoevers, Robert A.; Dalfsen, Jens H. van (Clinical psychopharmacology and neuroscience, 2025)
Objective: Intranasal (IN) esketamine represents a novel add-on treatment for treatment-resistant depression (TRD) with reported favourable effects on insomnia. IN esketamine treatment might similarly reduce the incidence of insomnia as an adverse event (AE). The present meta-analysis therefore investigated whether IN esketamine relative to placebo is associated with a lower incidence of insomnia as an AE in adults with TRD. Methods: Data were retrieved from seven randomised placebo-controlled trials evaluating the safety and efficacy of IN esketamine combined with a monoaminergic antidepressant in the treatment of TRD that reported data on insomnia as an AE. The study population (n = 1,311) comprised adult patients (aged ≥ 18 years) with a primary diagnosis of major depressive disorder. A mixed-effects logistic regression model was employed to compare the incidence of insomnia as an AE between the IN esketamine and placebo group. Results: Insomnia as an AE was reported by 52 patients (7.3%) in the IN esketamine group relative to 40 (6.7%) in the placebo group. IN esketamine compared to placebo was not associated with the odds of insomnia as an AE (OR = 1.07; 95% CI = 0.68−1.69; p = 0.76). There was no evidence for heterogeneity between the included trials. Conclusion: IN esketamine does not affect the occurrence of insomnia as an AE in the treatment of TRD. This contrasts previous findings demonstrating beneficial effects of esketamine on insomnia severity relative to placebo, although AE reporting may not capture insomnia improvements in a population with frequent baseline insomnia
Gesehen am 04.11.2025